Biosynthesis Of Silver Nanoparticles Using Cassava Leaves Aqueous Extract - Kananiasan, Gopal (Universiti Sains Malaysia, 2018)
Silver nanoparticles can be synthesized using physical, chemical and biological pathway. As compared to these three methods, biological approach is easier, more environmentally friendly and low cost. This study emphases on biosynthesis of silver nanoparticles using Cassava leaf extract as reducing and stabilizing agents. Aqueous silver ions, Ag+ when exposed to plant leaf extract were reduced to silver metal, Ag and resulted in a colour change from colourless to brown indicating the formation of silver nanoparticles. The synthesized silver nanoparticles were characterized by UV-Vis Spectroscopy, Surface Electron Microscopy (SEM), Energy Dispersive X-ray Spectroscopy (EDX), Dynamic Light Scattering (DLS) and Zeta Potential Analysis techniques. The UV-vis spectrum of sample containing synthesized silver showed gradual increase of surface plasmon resonance peak intensity at 430 nm to 435 nm. A few parameters such as plant extract concentration, volume ratio of plant extract to concentration of silver nitrate and silver nitrate concentration have been studied and show the same range of wavelength at maximum absorption. The highest absorbance, 2.00 was obtained after 3 days using 2 mM silver nitrate react with 1 wt% plant extract in ratio of 1:5. Zeta Potential Analysis for silver nanoparticles’ stability shows the value of -15.8 mV. The hydrodynamic size distribution was analyzed using DLS which gives average Z-diameter values at the range between 12 nm to 1000 nm.